MEKANISME CORPORATE GOVERNANCE, MANAJEMEN LABA DAN KINERJA KEUANGAN (Studi Pada Perusahaan Go-Publik Sektor Manufaktur) - Luluk M. Ifada; Gigih Kurniawan (Jurnal Ekonomi dan Bisnis, 2011)
The principal purpose of this study was to examine the influence of corporate governancemechanism with earnings management and influence concequensies of earnings managementto financial performance. Measurement of corporate governance mechanism consist of: institutionalownership, managerial ownership, presence of independent of director and size of director.Institutional ownership, manajerial ownership and presence of independent of director canaffect the action of earning management, which caused in the use of discretionary accruals intothe lower. Whereas the small size of director would be more effective in performing supervisoryaction of earnings management. Earnings management is conducted by managers on firmfundamental factors, namely the nterventon on making of financial statement based on accrualaccounting. So that eranings management will affect performed by managers on the factors- fundamental factors the company, by intervention in the preparation of financial statementsbased on accrual accounting. So that earnings management will affect financial performance.The populations of this research is all of companies in the manufacturing sector at the IndonesianStock Exchange, which were published in financial report from 2005-2007. Purposive samplingmethod was used to determine research sample. From this method, we have collected 37observations.By using multiple regression analysis as the research method, the findings are: manajerial ownershipinfluence negatively to earnings management and size of director influence positively toearning management as hypothesized. Institutional ownership and presence of independentof director had not significant influence to earnings management. Earning management havesignificant effects on financial performance.Keywords: corporate governance mechanism, eearnings management and financial performance